Pemeriksaan Tekanan Darah Dan Penyuluhan Tentang Hipertensi Di Desa Pragak Kecamatan Parang Kabupaten Magetan - Adhin Al Kasanah; Tantri Arini (Lembaga Pengembangan Kinerja Dosen, 2023)
Hypertension is a non-communicable disease whose prevalence continues to increase. Many hypertensive sufferers have no complaints, so sufferers do not know that they have hypertension, but then find themselves having complicating diseases or complications of hypertension, so that it is a deadly disease or also called a silent killer. Therefore efforts are needed to deal with hypertension. The purpose of this community service is to carry out blood pressure checks and counseling on hypertension. The method used in this counseling is the lecture method using media leaflets. The results of blood pressure checks showed that 25% of the people who participated in this activity had blood pressure of more than 140/90 mmHg. The results of the pre-test score showed a value of 63.5 and a post-test score of 92.7. This shows an increase in the value of knowledge about hypertension after counseling.